Genome‐wide occupancy of histone H3K27 methyltransferases CURLY LEAF and SWINGER in Arabidopsis seedlings. (31st January 2019) - Shu, Jie; Chen, Chen; Thapa, Raj Kumar; Bian, Shaomin; Nguyen, Vi; Yu, Kangfu; Yuan, Ze‐Chun; Liu, Jun; Kohalmi, Susanne E.; Li, Chenlong; Cui, Yuhai
Abstract: The Polycomb Group (PcG) proteins form two protein complexes, PcG Repressive Complex 1 (PRC1) and PRC2, which are key epigenetic regulators in eukaryotes. PRC2 represses gene expression by catalyzing the trimethylation of histone H3 lysine 27 (H3K27me3). In Arabidopsis ( Arabidopsis thaliana ), CURLY LEAF (CLF) and SWINGER (SWN) are two major H3K27 methyltransferases and core components of PRC2, playing essential roles in plant growth and development. Despite their importance, genome‐wide binding profiles of CLF and SWN have not been determined and compared yet. In this study, we generated transgenic lines expressing GFP‐tagged CLF/SWN under their respective native promoters and used them for ChIP‐seq analyses to profile the genome‐wide distributions of CLF and SWN in Arabidopsis seedlings. We also profiled and compared the global H3K27me3 levels in wild‐type (WT) and PcG mutants ( clf, swn, and clf swn ). Our data show that CLF and SWN bind to almost the same set of genes, except that SWN has a few hundred more targets. Two short DNA sequences, the GAGA ‐like and Telo ‐box‐like motifs, were found enriched in the CLF and SWN binding regions. The H3K27me3 levels in clf, but not in swn, were markedly reduced compared with WT; and the mark was undetectable in the clf swn double mutant. Further, we profiled the transcriptomes in clf, swn, and clf swn, and compared that with WT. Thus this work provides a useful resource for the plant epigenetics community for dissecting the functions of PRC2 in plant growth and development.